Product and Channel Difference Mofel Distribution in Increasing Customer Loyalty - Sri Rezeki; Lili Suryati; Wikrama Wardana; Desamen Simatupang; Marihot Simanjuntak; Brenhard Tampubolon; Mauritz Sibarani (Greenation International Journal of Tourism and Management, 2023)
This study aims to determine the effect of product differentiation on customer loyalty at CV. Makmur Auto Sejahtera Medan, knowing the effect of distribution channels on customer loyalty at CV. Makmur Auto Sejahtera Medan, and knowing the effect of product differentiation and distribution channels on customer loyalty at CV. Prosperous Auto Prosperous Medan. The population in this study are regular customers of CV. Prosperous Auto Sejahtera Medan as many as 62 regular customers. The sampling technique in this study used a saturated sample. Thus, the number of research samples used is 62 regular customers. Data were analyzed using multiple linear regression analysis method. The results of the analysis give the equation Customer Loyalty = 0.108 + 0.249 Product Differentiation + 0.383 Distribution Channels + e. The results of the research partially show that product differentiation has a positive and significant effect on customer loyalty CV. Prosperous Auto Prosperous Medan. This is evidenced by the acquisition of tcount 4.834 > ttable 1.67065 and a significant value of 0.000 <0.05 and distribution channels have a positive and significant effect on customer loyalty CV. Prosperous Auto Prosperous Medan. This is evidenced by the acquisition of a tcount of 4.818 > ttable of 1.67065 and a significant value of 0.000 <0.05. Simultaneously, product differentiation and distribution channels simultaneously have a positive and significant effect on customer loyalty CV. Prosperous Auto Prosperous Medan. This is evidenced by the acquisition of an Fcount of 30.308 > ttable of 3.15 and a significant value of 0.000 <0.05.